2007
DOI: 10.1175/jcli3991.1
|View full text |Cite
|
Sign up to set email alerts
|

Convective Precipitation Variability as a Tool for General Circulation Model Analysis

Abstract: Precipitation variability is analyzed in two versions of the Community Atmospheric Model (CAM), the standard model, CAM, and a "multiscale modeling framework" (MMF), in which the cumulus parameterization has been replaced with a cloud-resolving model. Probability distribution functions (PDFs) of daily mean rainfall in three geographic locations [the Amazon Basin and western Pacific in December-February (DJF) and the North American Great Plains in June-August (JJA)] indicate that the CAM produces too much light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
106
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 108 publications
(116 citation statements)
references
References 37 publications
10
106
0
Order By: Relevance
“…When the same 15 min data are plotted using 1 • values (not shown), the plots look very similar to the 3 h average 1 • grid, showing that this is a horizontal and not a temporal resolution dependence. A likely explanation for this is that, although on larger scales the average precipitation is constrained by radiative-convective equilibrium (and therefore agrees well with both M in the model and the preferred rain rate in the warm pool region in DeMott et al (2007)), on smaller scales there is some mesoscale circulation feedback that allows some grid cells to rain at a consistently heavier rate at the expense of moredistant cells (typically, the heavier rain in the model occurs along lines of low-level convergence). Field and Shutts (2009) found that instantaneous rain rates from UM operational forecasts with parametrized convection actually had too many instances of heavy rain relative to an idealized CSRM and satellite data.…”
Section: Precipitation Distributionssupporting
confidence: 57%
See 4 more Smart Citations
“…When the same 15 min data are plotted using 1 • values (not shown), the plots look very similar to the 3 h average 1 • grid, showing that this is a horizontal and not a temporal resolution dependence. A likely explanation for this is that, although on larger scales the average precipitation is constrained by radiative-convective equilibrium (and therefore agrees well with both M in the model and the preferred rain rate in the warm pool region in DeMott et al (2007)), on smaller scales there is some mesoscale circulation feedback that allows some grid cells to rain at a consistently heavier rate at the expense of moredistant cells (typically, the heavier rain in the model occurs along lines of low-level convergence). Field and Shutts (2009) found that instantaneous rain rates from UM operational forecasts with parametrized convection actually had too many instances of heavy rain relative to an idealized CSRM and satellite data.…”
Section: Precipitation Distributionssupporting
confidence: 57%
“…The 4 km 3Dsmag model exhibits cooling and moistening at mid-levels and warming and drying at low levels, while the 12 km param model shows much less, with perhaps slight warming and moistening at low levels for subgrid terms. Looking only at what convection does directly (the subgrid terms), the 4 km 3Dsmag model would seem to take longer in the transition to deeper convection, while the 12 km param model might transition to deep convection more quickly (especially given its tendency to rain at profiles with dryer mid-levels anyway, likely due to small entrainment rates) and therefore might consume CAPE more quickly and not maintain extended heavy precipitation because the CAPE never builds up, similar to arguments from DeMott et al (2007). However, it is not as simple as arguing that rainfall occurs only in moister tropospheric conditions, since the 4 km 2Dsmag model still gets the rainfall distribution right.…”
Section: Heating and Moistening Rates By Rain Ratementioning
confidence: 57%
See 3 more Smart Citations